1575.42 MHz Frequency Utilization on Intelligent Transportation System in Car Monitoring Distribution Delivery Logistic Using ublox GPS Neo 6M - Shidqi Ramadhandy Rizqulloh; Ridwan Satrio Hadikusuma; Ulinnuha Latifa (Fakultas Teknik, Universitas Jember, 2022)
Intelligent Transportation System or a smart transportation system with new technology that has been growing in recent years which is used as a computing system and communication technology for various purposes, such as traffic management, vehicle and highway security and emergency services. The current growth of e-commerce is very powerful, because people have placed e-commerce as a lifestyle. The high demand for logistics and delivery causes the need for monitoring package cars. This research system is designed to automatically monitor package cars, by utilizing the receiver frequency in the L1 frequency band (1575.42 MHz) which is modulated by the Ublox GPS Neo 6M module. Accelerometer sensors and acoustic data are used in cars as speed gauges and are used to detect and provide brief recordings in the event of an accident and can also monitor the speed of the car's distribution of packages in real-time. It was obtained for 7 trials with the same speed and constantly to avoid the Doppler effect that the accuracy of the GPS was quite good and the data was successfully uploaded to the web server in real time.